Novel Protein-Repellent and Antibacterial Resins and Cements to Inhibit Lesions and Protect Teeth - Li Cao; Junling Wu; Qiang Zhang; Bashayer Baras; Ghalia Bhadila; Yuncong Li; Mary Anne S. Melo; Michael D. Weir; Yuxing Bai; Ning Zhang; Hockin H. K. Xu (International Journal of Polymer Science)
Orthodontic treatment is increasingly popular as people worldwide seek esthetics and better quality of life. In orthodontic treatment, complex appliances and retainers are placed in the patients’ mouths for at least one year, which often lead to biofilm plaque accumulation. This in turn increases the caries-inducing bacteria, decreases the pH of the retained plaque on an enamel surface, and causes white spot lesions (WSLs) in enamel. This article reviews the cutting-edge research on a new class of bioactive and therapeutic dental resins, cements, and adhesives that can inhibit biofilms and protect tooth structures. The novel approaches include the use of protein-repellent and anticaries polymeric dental cements containing 2-methacryloyloxyethyl phosphorylcholine (MPC) and dimethylaminododecyl methacrylate (DMAHDM); multifunctional resins that can inhibit enamel demineralization; protein-repellent and self-etching adhesives to greatly reduce oral biofilm growth; and novel polymethyl methacrylate resins to suppress oral biofilms and acid production. These new materials could reduce biofilm attachment, raise local biofilm pH, and facilitate the remineralization to protect the teeth. This novel class of dental resin with dual benefits of antibacterial and protein-repellent capabilities has the potential for a wide range of dental and biomedical applications to inhibit bacterial infection and protect the tissues.